Safety and Efficacy of Sodium Nitroprusside During Prolonged Infusion in Pediatric Patients. Issue 5 (June 2015) - Hammer, Gregory B.; Lewandowski, Andrew; Drover, David R.; Rosen, David A.; Cohane, Carol; Anand, Ravinder; Mitchell, Jeff; Reece, Tammy; Schulman, Scott R.
<x xml:space="preserve">Abstract</x> Objective: Sodium nitroprusside is a direct-acting vasodilator used to lower blood pressure in the operating room and ICU. The efficacy of sodium nitroprusside has been analyzed in few pediatric randomized trials. This study assesses the efficacy and safety of sodium nitroprusside following at least 12 hours of IV infusion in children. Design: Randomized, double-blind withdrawal to placebo study. Setting: ICUs. Patients: Pediatric patients younger than 17 years. Interventions: Following 12–24 hours of open-label sodium nitroprusside titration, a blinded infusion of sodium nitroprusside or placebo was administered (at the stable rate used at the end of the open-label phase) for up to 30 minutes. Measurements and Main Results: The primary efficacy measure was whether control of mean arterial blood pressure was lost, that is, increased above ambient baseline for two consecutive minutes during the blinded phase. The proportion of patients who lost mean arterial blood pressure control in the placebo group (15/19; 79%) was significantly different than those in the sodium nitroprusside group (9/20; 45%) (p = 0.048). Three patients experienced rebound hypertension during the blinded phase, and all were in the placebo group. Serious adverse event rates were low (7/52; 13%), and in only one patient was the serious adverse event determined to be related to sodium nitroprusside by the site investigator. Fourteen patients (27%) had whole blood cyanide levels above 0.5 μg/mL, with high correlation (0.7) between infusion rate and cyanide levels, but there were few clinical signs of cyanide toxicity. Conclusions: Sodium nitroprusside is efficacious in maintaining mean arterial blood pressure control in children following a 12-hour infusion. Although a high proportion of patients were found to have elevated cyanide levels, toxicity was not observed.